2020
DOI: 10.3390/molecules25061333
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Based Dynamic Approach to Assess Bioaccessible Zinc in Dry Dog Food Samples

Abstract: This work proposes a simple and easy-to-use flow-through system for the implementation of dynamic extractions, aiming at the evaluation of bioaccessible zinc and the characterization of leaching kinetics in dry dog food samples. The kinetic profile of Zn extraction was determined by flame atomic absorption spectroscopy and the results were fitted in an exponential function (R2 > 0.960) compatible with a two first-order reactions model. Values of fast leachable Zn ranged from 83 ± 1 to 313 ± 5 mg of Zn per k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The inorganic forms of Zn are also more sensitive to dietary Ca and phytate (Cummings and Kovacic 2009 ). According to a recent study, only 58.2 % of the total Zn content in dry dog foods was bioavailable to dogs (Gregório et al 2020 ). Anyway, the content of Ca, phytate, and Zn in the dogs’ diets were not assessed in this study, and thus, further research is needed to explain the reason for higher hair Zn concentration in raw diet fed dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The inorganic forms of Zn are also more sensitive to dietary Ca and phytate (Cummings and Kovacic 2009 ). According to a recent study, only 58.2 % of the total Zn content in dry dog foods was bioavailable to dogs (Gregório et al 2020 ). Anyway, the content of Ca, phytate, and Zn in the dogs’ diets were not assessed in this study, and thus, further research is needed to explain the reason for higher hair Zn concentration in raw diet fed dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the fast method proposed by Goi et al [ 14 ], our approach provides the value of the total Zn as a digestion process is performed before the fluorimetric reaction while the near-infrared reflectance spectroscopy-based method can only detect Zn associated with organic complexes, providing underestimated results for dog food supplemented with inorganic forms of Zn. Finally, compared to other approaches that applied AAS [ 26 ] or ICP-MS [ 7 ], the method proposed here allows the simultaneous determination of up to 96 samples, without requiring expensive equipment or application of the standard addition method.…”
Section: Resultsmentioning
confidence: 99%
“…As well as this, high levels of Ca in the diet can inhibit the absorption of Fe and Zn in the gastrointestinal tract [69]. Recent studies on the development of a new system for the evaluation of bioaccessible Zn in dry dog food, showed that most of the foods presented total Zn levels higher than the MLL, but this value was not surpassed if the bioaccessible Zn content was considered [70]. Therefore, it should be borne in mind that the bioavailability of trace minerals determines efficacy.…”
Section: Trace Elementsmentioning
confidence: 99%